ANALISIS TINGKAT KESESUAIAN PENERAPAN SISTEM PROTEKSI KEBAKARAN DAN SARANA PENYELAMATAN JIWA DI RUMAH SAKIT PUSAT OTAK NASIONAL TAHUN 2023 - Hana Nabilah Aprillia, (2023)
The National Brain Center Hospital had been ready to prevent and control fire by implementing a fire protection system and life-saving facilities. Based on the preliminary study, it was found several discrepancies in the components of the active fire protection system. The purpose of this study was to analyze the application of fire protection systems and life-saving facilities at the National Brain Center Hospital. The method used in this research was descriptive with a qualitative approach through interviews and observations. The selection of informants used purposive sampling technique based on certain criteria consisting of 1 key informant, 2 main informants and 1 supporting informant. The results showed that the level of fulfillment of the passive protection system obtained a percentage of 68.75% and was included in the sufficient category which meant that it was installed but a small number of components did not meet the requirements, the level of fulfillment of the active protection system obtained a percentage of 83.90% and was included in the good category which met to the requirements, and the level of fulfillment of life-saving facilities was a percentage of 78.88% and it was included in the sufficient category which meant it was installed enough but a small number of components did not meet the requirements. The results showed that the reliability value of the hospital building was in accordance with the applicable requirements; However, there were still some deficiencies found in the components of the active protection system and life-saving facilities. Therefore, hospitals must increase readiness in fire prevention and control efforts.